Pretend play as abstraction: Implications for early development and beyond. (April 2023) - Gleason, Tracy R.; White, Rachel E.
Abstract: Humans are the only species that engages in sustained, complex pretend play. As pretend play is practically ubiquitous across cultures, it might support or afford a context for developmental advances during the juvenile period that have implications for functioning in adulthood. Early in development, learning to separate our thoughts from reality is practiced in pretend play and is associated with changes not just in cognition, but in emotional and social domains as well. Specifically, pretend play affords opportunities to engage in abstractions that could support abilities such as perspective-taking, emotion recognition and regulation, and cooperation and negotiation in childhood. In turn, the abstraction skills promoted by early pretend play might underlie creativity, innovation, and our capacity to feel empathy and moral obligation to others in later childhood and adulthood. In fact, because pretend play affords sharing our abstractions with others, it might be an early context for behaviors that ultimately promote the shared abstractions of human culture itself.